Strategic Aspects of Voluntary Disclosure Programs for Corruption Offences: Towards a Design of Good Practice - Mathias Nell (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
Even though high penalties for corruption offences have a deterrent and preventive effect, they also entrap bribe-takers and bribe-givers in their corrupt relationship. Moreover, pending penalties can be misused to make threats against opportunistic behavior and can thus stabilize risky bribe agreements. This paper shows how voluntary disclosure programs can be strategically applied to break the 'pact of silence' and to promote opportunism in a targeted way. Against this background the paper studies the leniency provisions in the penal codes of 56 countries. The analysis reveals deficiencies in the utilization and in the design of voluntary disclosure programs for corruption offences.
Keywords: K14; L14; 330; Corruption; Criminal Law; Leniency; Self-Reporting; Voluntary Disclosure Program